Pengaruh Pengenalan Lapangan Persekolahan (PLP) Terhadap Soft Skills Dengan Dimoderasi Oleh Jenis Kelamin Pada Mahasiswa Calon Guru - Cahyaningsih, Diyah; Kristiani, Kristiani; Noviani, Leny (Universitas Negeri Surabaya, 2024)
The research aims to determine the effect of Introduction to the Schooling Field (PLP) on soft skills moderated by gender in students of the Office Administration Education, Accounting Education, and Economic Education Study Program at UNS involved 183 students from the 2018-2019 class who had taken part in PLP activities. The sampling technique in this research used proportional random sampling with data collection through questionnaires. The sub-group moderation method is used as a data analysis technique. The results obtained in this research are: (1) There is a positive and significant influence between PLP and soft skills. (2) Gender does not strengthen the influence of PLP on soft skills. The research results show that the PLP's ability to influence soft skills is very weak, this is because there is a gap between the soft skills competency score and the final PLP score.